Influence of slip condition on peristaltic transport of a viscoelastic fluid with fractional Burgers' model - Tripathi, D.; Gupta, P.K.; Das, S. (My University, 2011)
The investigation is to explore the transportation of a viscoelastic fluid with fractional Burgers' model by peristalsis through a channel under the influence of wall slip condition. This analysis has been carried out under the assumption of long wavelength and low Reynolds number. An approximate analytical solution of the problem is obtained by using homotopy analysis method. It is assumed that the cross-section of the channel varies sinusoidally along the length of the channel. The expressions for axial velocity, volume flow rate, and pressure gradient are obtained. The effects of the fractional parameters α and β, material constants λ1, λ2, λ3, slip parameter k, and amplitude φ on the pressure difference and friction force across one wavelength are discussed numerically and with the help of illustrations.
Keywords: Fractional Burgers' fluid; Friction force; Homotopy analysis method; Peristalsis; Pressure difference